(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The job satisfaction of BPO employees has been a topic of significant interest in recent years, given the fast-paced and high-pressure nature of the work environment. BPO or Business Process Outsourcing is a growing industry in which companies outsource various business functions, such as customer service, telemarketing, and technical support, to third-party service providers. Research suggests that job satisfaction among BPO employees is influenced by several factors, including the nature of the job itself, the work environment, the relationship with colleagues and supervisors, compensation and benefits, and opportunities for growth. Most of the respondents are 26-30 years old, working in BPO with 4-6 years in service, and the respondents are college graduates. The survey researchers provided the "Effect of job mismatch in job satisfaction on the employer’s salary, work environment, compensation, benefits, and co-workers relationship’" the data says they are very satisfied with their jobs as BPO employees. Who is most likely to have job satisfaction in terms of sex based on the result? Men were very satisfied with their job and got a mean score of 3.37, while females were satisfied only and got a mean score of 3.02. Based on the findings of the studies and the results. The researchers recommend conducting a seminar for fresh graduates and job seekers and inviting a speaker to the seminar to promote or inform about our research entitled The Effect of Job Mismatch on Job Satisfaction of BPO Employees. The Job Mismatch no longer affects their satisfaction in their job, and working in BPO, even if you are a fresh graduate, is fine as long as you know that you are happy and satisfied.